Enseigner la méthodologie de la recherche en technologie éducative : des conceptions aux concepts seuils - Barbara Class; Daniel Schneider; Mona Laroussi; François Lombard (Distances et Médiations des Savoirs, 2016)
Training novice researchers in research methodology requires taking into account their research conceptions. This pilot study was conducted next to the training of seize doctoral applicants from the MIRRTICE doctoral incubator. It reports results gathered with the French version of the Students’ Conceptions of Research Inventory (Meyer et al., 2005). Qualitative and quantitative results show that for the majority of students (n=13) research method is conceived in terms of research process. They also conceive research in a transformative perspective for them, their discipline and society as a whole. Only two students share misconceptions. Factor analysis unveils misconceptions regarding research ethics. These results encourage us to design the next edition of the research methodology course with a model that takes into account and connects conceptions and threshold concepts.